Analysis of The Effect of Qris Usage, E-Commerce, and Capital on MSMEs Income in Tabanan Regency - Gusti Ayu Leela Laksmi Devana; Surya Dewi Rustariyuni (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in Tabanan Regency has been driven by economic development, digitalization, and changes in consumer behavior following the COVID-19 pandemic. Despite the continuous increase in the number of MSMEs each year, business owners face significant challenges, such as limited adoption of digital technologies, increasing market competition, and restricted access to working capital. This study aims to analyze the effect of QRIS usage, e-commerce, and capital on MSME income both simultaneously and partially in Tabanan Regency. A quantitative method was employed using multiple linear regression analysis. The sample was determined using a non-probability sampling method with an accidental sampling approach. The results show that QRIS, e-commerce, and capital simultaneously have a significant effect on MSME income in Tabanan Regency. Partially, QRIS usage and capital have a positive and significant effect on income, while e-commerce does not have a significant partial effect. This indicates that although e-commerce can expand market reach, intense competition and limited technological literacy among the local population hinder its impact on MSME income in the region.